2014
DOI: 10.1210/jc.2013-3918
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cholesterol Efflux Capacity and Atherogenic Lipid Profile in Young Women With PCOS

Abstract: Our novel findings of decreased cholesterol efflux and an atherogenic lipid particle number and size pattern in women with PCOS, independent of obesity, further substantiate the increased risk of CVD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…7,[20][21][22] Only one report has examined both men and women. 7 Similar to our findings, the Multi-Ethnic Study of Atherosclerosis (MESA) also reported that higher SHBG levels were associated with a less atherogenic profile in both men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[20][21][22] Only one report has examined both men and women. 7 Similar to our findings, the Multi-Ethnic Study of Atherosclerosis (MESA) also reported that higher SHBG levels were associated with a less atherogenic profile in both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, greater total T levels correlated with lower HDL in another report, but associations between SHBG and lipid subfractions were not reported. 20 Strengths of this report include the novel assessments of lipid subfractions and sex hormone profiles in Asian Indians, a population at high risk for atherogenesis. The cohort, while small, was also population-based rather than referral center based.…”
Section: Discussionmentioning
confidence: 99%
“…It can coexist with increased small low-density lipoprotein particles and an otherwise normal lipid profile (156). A study reported that cholesterol efflux capacity from macrophages, a measure of high-density lipoprotein-cholesterol function and an independent predictor of subclinical CVD, is abnormally suppressed in women with PCOS (157).…”
Section: E Cardiovascular Disease Riskmentioning
confidence: 99%
“…Recent data have shown that cholesterol efflux capacity, a new biomarker that characterizes a key step in reverse cholesterol transport, is inversely associated with the risk of future cardiovascular events in a large population-based cohort of adults [71]. Interestingly, a recent study has reported that PCOS women have a decreased cholesterol efflux capacity and reduced atherogenic lipid particle number and size, independently of body weight [72]. Similar evaluations among NAFLD patients will be needed in the near future, because these patients, like PCOS women, are at high risk for cardiovascular disease [3-6, 47, 52, 73].…”
Section: Research Agendamentioning
confidence: 99%